PWE-058 Tissue Acquisition from Solid Pancreatic Lesions – Endoscopy or Surgery. (4th June 2013) - Nayar, M; Kung, D Tai; Haugk, B; White, S; Manas, D; Jaques, B; Sen, G; French, J; Charnley, R; Oppong, K
Abstract : Introduction: The accurate diagnosis of solid pancreatic masses is important in directing appropriate management of patients. The methods commonly used are percutaneous, laparoscopic and EUS guided biopsy of these lesions. Laparoscopic guided biopsy consumes theatre time and space and can be more expensive than the alternatives. In our unit; laparoscopic guided biopsy is reserved for patients who have an inconclusive result from an EUS guided biopsy or are considered for trial resection. The aim of this study was to look at the diagnostic performance of endoscopic ultrasound (EUS) guided biopsy (fine needle aspiration (FNA) or pro-core biopsy) and laparoscopic (lap) guided biopsy of solid pancreatic masses in a large HPB referral centre. Methods: Retrospective review of patients undergoing EUS or laparoscopic guided biopsy for solid lesions between January 2011 and March 2012. Data was obtained from a dedicated prospectively maintained database in the histopathology department. Final diagnosis was based on positive histology/cytology of pancreatic adenocarcinoma. Benign cases were followed up for a period of at least six months. Results: 464 specimens from the pancreas (histology + cytology including pancreatic resections) were received by the histopathology department during this period. Of these 275/464 (59%) patients had tissue biopsy of solid lesions. These included: EUS guided biopsy = 253 and Laparoscopic guided biopsy = 22. In the latter group; 10/22(45%) had a previous EUS of which 8/10 had an accurate diagnosis. 12/22(54%) patients went straight for laparoscopic guided biopsy. For the purposes of this study; highly suspicious and malignant samples were categorised as malignant. The accuracy, sensitivity and negative predictive value for EUS guided biopsy and laparoscopic guided biopsy were 92%/96%; 90%/94% and 74%/89% respectively. The inadequate aspirate rate was 5% and 0% respectively. There was no significant difference between the two groups. The cost of performing these procedures in our trust were: EUS guided biopsy £1094 and lap guided biopsy £ 2164. Conclusion: In our unit;EUS guided biopsy of solid pancreaticobiliary lesions provides high diagnostic accuracy with a low inadequate aspirate rate. Our data supports the role of EUS guided FNA as the first modality of tissue acquisition from the pancreas. Though this data also shows the cost effectiveness of EUS guided biopsy over lap guide biopsy; in units with lower diagnostic accuracy of EUS guided biopsy the cost benefit may not be realised. Disclosure of Interest: None Declared.